Durability of the adhesive bond in cross-laminated northern hardwoods and softwoods. (8th November 2021) - Musah, Munkaila; Wang, Xiping; Dickinson, Yvette; Ross, Robert J.; Rudnicki, Mark; Xie, Xinfeng
Highlights: Bond durability of both hardwood and mixed species cross-laminations using melamine- and resorcinol-based adhesive systems were evaluated. Mixed hardwood species provided durable bonds for manufacturing cross-laminated timber. Resorcinol adhesive appeared to be suitable for cross-laminating mixed hardwood species. Mixed hardwood species generally produced higher bond performance than single species cross laminations. Abstract: In this study, we investigated the durability of adhesive bonds in the cross-laminated lumber of seven hardwood and two softwood species from the Great Lakes region. The 2-layered cross-laminations were glued using phenol resorcinol- and melamine-based structural adhesives. A total of 720 cross-laminated wood blocks were tested for delamination by exposing the samples to cyclic (wet-dry) conditions. Distribution of the adhesive on the bondlines was also studied to understand the effect of adhesive penetration on bond durability. The results indicated that mixed hardwood cross-laminations generally produced better bonds than single hardwood species cross-laminations. Hardwood and softwood hybrid cross-laminations were found to have better bond durability in dry-wet cycles. A high failure rate (≥ 50%) was found in the following single species cross-laminations: aspen, white ash, white pine, and yellow birch. Similarly, several mixed species cross-laminations resulted in a delamination rate of 50% and higher, which raises caution in their use in CLT manufacturing. In addition, the viscosity of the adhesive influences the maximum depth of penetration, which tends to affect the durability of adhesive bonds.